2022
DOI: 10.2217/fmb-2022-0049
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Actinotignum Schaalii Infections in a Large Canadian Healthcare Region

Abstract: Aims: We characterize the epidemiology of Actinotignum schaalii within a large Canadian region after implementation of improved identification methods. Patients & methods: Positive cultures for A. schaalii from a centralized microbiology laboratory in Canada were analyzed. Clinical data were retrieved through administrative databases and chart reviews. Primary outcome was incidence of A. schaalii infections; secondary outcomes included mortality, hospital admission and length of stay. Results & conclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Data on infections due to this pathogen are scarce, with most reported cases being from UTI. Moreover, few reviews [ 20 ] concerning A. schaalii have been published, with most being a short series of cases, and ours being the most extensive to our knowledge, with 107 infectious episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Data on infections due to this pathogen are scarce, with most reported cases being from UTI. Moreover, few reviews [ 20 ] concerning A. schaalii have been published, with most being a short series of cases, and ours being the most extensive to our knowledge, with 107 infectious episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Calgary Laboratory Services (CLS) (now Alberta Precision Laboratories [APL]) is a centralized regional microbiology laboratory providing ambulatory and hospital-based testing to Calgary and the Alberta Health Services (AHS) South Zone, covering a population of 2.0 million ( 18 ). Basic demographic data for A. schaalii isolates, such as patient age and sex, were derived from the previously completed clinical study for the purposes of microbiological characterization ( 14 ). Infectious diagnosis, hospitalization, and 90-day mortality rates were determined through a retrospective chart review of the patients’ electronic medical records, which was independently performed by two investigators (J.M.…”
Section: Methodsmentioning
confidence: 99%
“…( 1 , 12 , 13 ). We previously performed a comprehensive study of the clinical manifestations and population-based epidemiology of clinically relevant infections due to A. schaalii in our health care region ( 14 ). In this study, we conducted a detailed microbiological analysis of the previously described isolates to improve our understanding of the genotypic and phenotypic characteristics of this organism.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial infections, particularly infections caused by Staphylococcus aureus , are the predominant etiology of this type of abscess ( Talan et al., 2016 ). However, recent studies have also indicated that skin abscesses can also be caused by anaerobic or facultative anaerobic bacteria ( Accetto and Avguštin, 2021 ; Mah et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is easily overlooked because of its special growth requirements. Recently, the utilization of advanced equipment within clinical microbiology laboratories has led to increasing recognition of A. schaalii as an opportunistic pathogen that is commonly associated with urinary tract infections, bloodstream infections, and Fournier’s gangrene ( Yassin et al., 2017 ; Mah et al., 2022 ). However, abscess formation caused by A. schaalii is still rare ( Panganiban and Gupta, 2020 ).…”
Section: Introductionmentioning
confidence: 99%